FAKTOR PENGHAMBAT IMPLEMENTASI KURIKULUM MERDEKA DI SDN SALAM BABARIS - Insaniyah (Cangkal : Jurnal Ilmu Sosial Dan Humaniora, 2025)
The Merdeka Curriculum is designed with diverse intracurricular learning, giving students enough time to understand concepts and develop competencies. However, interviews with teachers at SDN Salam Babaris 4 revealed obstacles in its implementation. This study aims to identify the inhibiting factors and solutions for implementing the Merdeka Curriculum at the school. Using a descriptive qualitative approach, data were obtained through observation and interviews, and analyzed inductively. The obstacles found include a lack of understanding among the principal and teachers regarding the Merdeka Curriculum and differentiated learning, limited time for creative learning, students’ lack of focus during prayer, damaged facilities, incomplete books, no library staff, low understanding of diagnostic assessments, some teachers without teaching certificates, difficulties in teacher guidance at the start of the semester, challenges in adjusting teaching modules to student characteristics, and unfamiliarity with the academic and project report formats. Proposed solutions include teacher working group (KKG) activities, workshops, and webinars; warning students; repairing facilities through coordination with the Education Office; assigning teachers as library staff; printing books from PPM resources; procuring books through BOS funding and parental donations; and utilizing e-books. This study is expected to serve as a reference for overcoming challenges in implementing the Merdeka Curriculum in primary schools.